ANALYSIS AND DIAGNOSTIC OF PROPPANT FLOWBACK IN THE ORITO FIELD, COLOMBIA - A VARELA; N SAAVEDRA (CT&F Ciencia, Tecnología & Futuro, 2000)
Hydraulic fracturing is a conventional practice for production enhancement in low production and damaged wells. Proppant flowback has been a concern in hydraulic fracturing since proppant began to be used as fracture supporting material. In order to prevent the usual proppant flowback problems, some wells in the Orito field were fractured using curable resin coated proppant (RCP). However, flowback production of proppant from some hydraulically fractured wells has caused some serious operational problems, demanding additional analysis of the problem and field handling procedures. This paper describes the laboratory tests and field considerations to design the tests, taken into account to analyze and diagnose the proppant flowback problem in the Orito field. Two types of tests were performed i.e., displacement and flowback. El fracturamiento hidraulico es una practica convencional para el mejoramiento de produccion en pozos de baja productividad y en pozos con daño. El retorno de proppant ha sido un tema de interes en fracturamiento hidraulico desde que el proppant empezo a usarse como material de soporte de fractura. Con el fin de prevenir los problemas usuales de retorno de proppant, algunos pozos del campo Orito fueron fracturados utilizando proppant con resina curable (RCP). Sin embargo, retorno de proppant de algunos pozos fracturados hidraulicamente ha causado serios problemas operacionales, requiriendo algunos analisis adicionales del problema y ciertos procedimientos de manejo. Este articulo describe las pruebas de laboratorio y las consideraciones de campo tenidas en cuenta en el diseno de las pruebas, para el analisis y el diagnostico del problema de retorno de proppant en el campo Orito. Se realizaron pruebas de desplazamiento y de retorno de proppant.